Revitalization Through Collaboration: Purdue Students Work with West Lafayette Public Library - Nick Schenkel (The University of Alabama, 2022)
Their excitement was infectious. The four graduate students who worked with our community archives collections at the West Lafayette Public Library in fall semester 2008 tore into their work with a passion and a curiosity that amazed me and my staff - and prompted us to see our archival collections, our library, and our city with new eyes and with new interest.